The geographic distribution of Argas (Persicargas) miniatus and Argas (Persicargas) persicus (Acari: Argasidae) in America, with morphological and molecular diagnoses from Brazil, Chile and Cuba - Muñoz-Leal, Sebastian; Venzal, José Manuel; Nava, Santiago; Reyes, Mercedes; Martins, Thiago F.; Leite, Romário C.; Vilela, Vinicius L.R.; Benatti, Hector R.; Ríos-Rosas, Daniela; Barros Battesti, Darci M.; González-Acuña, Daniel; Labruna, Marcelo B. (2018)
High similarity of morphological traits has historically overshadowed the identities and distributions of poultry-associated soft ticks Argas (Persicargas) miniatus and Argas (Persicargas) persicus in America. In order to model the occurrence of both parasites in the continent, in the current study we performed morphological and molecular analyses to identify ticks collected in hen houses from Brazil and northern Chile. Combining these results with literature data, and the examination of Argas allotments deposited in the tick collections “Coleção Nacional de Carrapatos Danilo Gonçalves Saraiva” (Brazil), the “Coleção Acarológica do Instituto Butantan São Paulo” (Brazil), and the “Colección Zoológica de la Academia de Ciencia de Cuba” (Cuba), we present a critical list with the localities where A. (P.) miniatus and A. (P.) persicus have been reported in the American continent. Our results confirmed the presence of A. (P.) miniatus in Brazil and Cuba, and A. (P.) persicus in Chile, which in particular, constitutes the first molecularly confirmed report of the later species for South America. Although A. (P.) miniatus and A. (P.) persicus have been documented in 21 American countries, the identity of some reports must still be considered as uncertain until detailed morphological and/or molecular studies are performed. When contrasted to a Köppen-Geiger climate classification, A. (P.) miniatus predominantly occurs in equatorial and A. (P.) persicus in arid climates. However, until undetermined reports of both species are correctly identified, any conclusion on their geo-climatological occurrence throughout the American continent would be rather speculative.